A turn-on fluorescence chemosensor based on a tripodal amine [tris(pyrrolyl-α-methyl)amine]-rhodamine conjugate for the selective detection of zinc ions. Issue 18 (1st July 2016) - Balamurugan, Rathinam; Chang, Wen-I; Zhang, Yandison; Fitriyani, Sri; Liu, Jui-Hsiang
Abstract : A tris(pyrrolyl-α-methyl)amine (H3 tpa ) and rhodamine-based conjugate (PR) served as a sensor for the selective detection of Zn 2+ and their application of imaging living cells were studied. Abstract : A novel tetradendate ligand derived from a tris(pyrrolyl-α-methyl)amine (H3 tpa ) and rhodamine-based conjugate (PR ) has been designed for use as a sensor, synthesized and characterized spectroscopically.PR (tris(5-rhodamineiminopyrrol-2-ylmethyl)amine) serves as a selective colorimetric as well as a fluorescent chemosensor for Zn 2+ in acetonitrile/water (1 : 1, v/v). In the presence of Zn 2+, PR exhibited obvious absorption (558 nm) and emission (577 nm) peaks whose intensity increased along with increasing Zn 2+ concentrations. Titration experiments revealed that a large excess of Zn 2+ was required to saturate the absorption ( λ max ) and emission intensities. Upon the addition of 1000 equivalents of Zn 2+, the fluorescence intensity of thePR underwent an ∼500-fold increase ( Φ f = 0.34) with the emission maximum at 580 nm. These kinetics studies demonstrated that the absorption and emission changes were proportional to the Zn 2+ concentration. The color of the solution changed from colorless to a dark pink color. The fluorescence of thePR -Zn 2+ complex can be reversibly restored by using ammonium water or by heating. Competitive ion tests revealed that the intensity ofPR -Zn 2+ was not suppressed by excess amounts of other metal ions. The counter anions did not exert obvious influences on the absorption and emission profiles. 1 H-NMR and FT-IR spectroscopic investigations ofPR andPR -Zn 2+ revealed that the pyrrole motifs, –C{N– groups and spirolactam of rhodamine B are capable of coordinating cation guest species. Because each arm of the tripodal ligand tautomerizes independently, only moderate fluorescence enhancement could be seen until all three –C{N– groups were coordinated by zinc, which may be due to the spirolactam ring opening mechanism of the rhodamine unit. Once all three –C{N– groups were locked by coordinating with excess of Zn 2+, the isomerization was arrested, andPR exhibited highly enhanced fluorescence. In addition, energy optimized structures ofPR were found to be cage-like by Gaussian 09, further supporting that it can access a large excess of Zn 2+ . Intriguingly, imaging of HeLa cells by using a confocal microscope revealed that thisPR probe could be used for biological applications.